2005
DOI: 10.1021/ma050489m
|View full text |Cite
|
Sign up to set email alerts
|

Thermogelling Poly(caprolactone-b-ethylene glycol-b-caprolactone) Aqueous Solutions

Abstract: Poly(caprolactone-b-ethylene glycol-b-caprolactone) (PCL-PEG-PCL) triblock copolymer aqueous solution (>15 wt %) undergoes the sol-gel-sol transition as the temperature increases from 10 to 60 °C. The mechanism and structure-property relationship of the sol-gel transition were investigated. In particular, compared with the PEG-PCL-PEG triblock copolymers recently reported by our group, PCL-PEG-PCL has (1) a synthetic advantage without a hexamethylene diisocyanate coupling step, (2) a wider gel window of over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
255
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(268 citation statements)
references
References 22 publications
7
255
2
Order By: Relevance
“…A similar trend was observed for a poly(caprolactone-b-ethylene glycol-b-caprolactone) (PCL±PEG±PCL) aqueous solution, which undergoes a sol-to-gel transition as the temperature increases to 30 C. [12] The viscosity of a gel steadily increases as the pH increases from pH 2±8 at the same concentration (20 wt.-% in water). The viscosity (g¢) of the aqueous polymer solution (30 wt.-%) at 37 C as a function of pH is shown in Figure 3a.…”
Section: ±1supporting
confidence: 65%
“…A similar trend was observed for a poly(caprolactone-b-ethylene glycol-b-caprolactone) (PCL±PEG±PCL) aqueous solution, which undergoes a sol-to-gel transition as the temperature increases to 30 C. [12] The viscosity of a gel steadily increases as the pH increases from pH 2±8 at the same concentration (20 wt.-% in water). The viscosity (g¢) of the aqueous polymer solution (30 wt.-%) at 37 C as a function of pH is shown in Figure 3a.…”
Section: ±1supporting
confidence: 65%
“…67 The difference was attributed to the different micellar structure. The core and the shell of the micelles formed in the ABA triblock copolymer consisted of the hydrophobic CL and the hydrophilic EO segments, respectively.…”
Section: Aba Versus Bab Triblock Copolymersmentioning
confidence: 99%
“…Recently, PEG-PCL-PEG and PCL-PEG-PCL (Scheme 5) triblock copolymers have been introduced, and aqueous solutions thereof showed a clear sol-to-gel-to-turbid sol transition with an increase in temperature. [31,32] DLS and 13 C NMR studies indicated that the clear sol-to-gel transition arose from micellar aggregation, whereas the gel-to-turbid sol transition was driven by the breakage of the core-shell structure. Because of differences in structural topology, PCL-PEG-PCL had a higher G 0 (10 000 Pa) ( Figure 4) than did PEG-PCL-PEG (100 Pa) ( Figure 5).…”
Section: Poly(ethylene Glycol) (Peg)/polyestermentioning
confidence: 99%